Civilian Endangerment and Human Shield Tactics in the Siege of Mariupol - Caecilia Patrice Yonandi; Lewiandy (Dinasti Research, 2024)
Among the dramatic events of the Russo-Ukrainian War was the Siege of Mariupol in 2022, with the use of human shield tactics and resulting human casualties among civilian populations. This study will therefore assess the extent of human shielding the Ukrainian and Russian forces to ascertain the effects on the civilian population, and zero in on the legal implications under international humanitarian law. A descriptive qualitative research approach was used in this research, whereby information was obtained through wide-scale literature research, specifically reports by international bodies, educational material, and journalistic information by trusted sources. Both parties have done much to bring war closer to civilians and deny humanitarian groups access to them: deploying military infrastructure near residential areas and refusing access and evacuations. Like in most conflicts, civilians have accounted for most of the casualties; destroyed structures in cities or other critical parts were not spared, which has serious humanitarian effects. The study concludes that the use of human shield tactics in Mariupol involves grave violations of IHL and, in this respect, underlines an urgent need for strict adherence to legal norms in the protection of civilians during hostilities.